2017
DOI: 10.1111/1750-3841.13676
|View full text |Cite
|
Sign up to set email alerts
|

Moisture‐Mediated Interactions Between Amorphous Maltodextrins and Crystalline Fructose

Abstract: The effects of coformulating amorphous maltodextrins (MDs) and crystalline fructose, a deliquescent solid, on the moisture sorption, deliquescence point (RH ), and glass transition temperature (T ) behaviors were determined. Moisture sorption profiles of binary fructose:MD mixtures and individual ingredients were generated using controlled relative humidity (RH) desiccators and by dynamic vapor sorption techniques. Blends exhibited synergistic moisture uptake at RHs below the RH of fructose, attributed to part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…The effect of microencapsulation and the addition of crystalline ingredients become more complicated to understand as also indicated by Ortiz and colleagues [ 16 , 33 ]. Generally, higher physical and chemical instability have been reported for blends of deliquescent crystalline and amorphous ingredients compared to individual amorphous components [ 34 ]. Ortiz and colleagues [ 16 , 33 ] found that the addition of citric acid to amorphous green tea powders resulted in a decrease in physical and chemical stability.…”
Section: Resultsmentioning
confidence: 99%
“…The effect of microencapsulation and the addition of crystalline ingredients become more complicated to understand as also indicated by Ortiz and colleagues [ 16 , 33 ]. Generally, higher physical and chemical instability have been reported for blends of deliquescent crystalline and amorphous ingredients compared to individual amorphous components [ 34 ]. Ortiz and colleagues [ 16 , 33 ] found that the addition of citric acid to amorphous green tea powders resulted in a decrease in physical and chemical stability.…”
Section: Resultsmentioning
confidence: 99%
“…However, caffeine hydrate could form if β‐caffeine is exposed to approximately 100% RH for several hours to days (Pirttimäki & Laine, 1994) or to liquid water during processing. The incorporation of caffeine hydrate into a packaged final product would result in a delayed release of water if the a w /RH in the product was below the caffeine hydrate → β‐caffeine boundary condition, and this release of water in a closed system could lead to undesirable water–solid interactions (e.g., deliquescence and glass transition lowering) that could cause clumping and degradation of labile compounds (Khankari & Grant, 1995; Mauer & Taylor, 2010; Thorat et al., 2017).…”
Section: Resultsmentioning
confidence: 99%
“…The interactions of water vapor with blends of amorphous solids and deliquescent crystals (not hydrate formers within the experimental space) were also found to vary based on formulation in a series of studies that used the deliquescent crystals sucrose, sodium chloride, and fructose and a series of amorphous maltodextrins with different molecular weights (Ghorab et al 2014a,b;Thorat et al 2017). In deliquescent crystalline-amorphous ingredient blends, there are two main options for moisture-mediated effects: (a) Significant water absorption into the amorphous matrix occurs first (because amorphous solids are often more hygroscopic at lower RHs) or (b) deliquescence of the crystalline compound occurs before significant plasticization of the amorphous compound.…”
Section: Challenges Encountered When Crystalline and Amorphous Solids...mentioning
confidence: 99%
“…The saturated solution forming on a crystal surface as it deliquesces has the potential to plasticize the amorphous matrix. Many blends of crystalline and amorphous ingredients have been found to sorb more water as RH increases than that predicted by an additive model, which resulted in lower T g s than were found for the single amorphous ingredient in the same environment (Ghorab et al 2014a,b;Thorat et al 2017). In sealed (packaged) systems, as shown in Figure 5, exposing a blend of crystalline and amorphous ingredients to increased temperatures resulted in increasing the a w of the amorphous compound to the extent that the a w crossed above the RH 0 of the crystalline ingredient and caused deliquescence of the crystal in the matrix (and complicated identification of the T g during thermal analysis) (Thorat et al 2017).…”
Section: Challenges Encountered When Crystalline and Amorphous Solids...mentioning
confidence: 99%
See 1 more Smart Citation